Modelo didáctico para el desarrollo del pensamiento matemático a través de la modelación matemática en situaciones de riesgo ambiental (2023)
Modelling has become one of the general processes of mathematical activity that allows enhancing mathematical thinking. For its part, mathematical thinking contributes to the development of logical reasoning, creativity, and allows the articulation of knowledge of different types and from different areas. In this sense, mathematics can help minimize environmental risks and use this didactic resource to motivate students towards their study.